The Role of Ethnoecological Knowledge, Climate Adaptation Strategies, and Farmer Innovation in Achieving Sustainable Agriculture in Indonesia - Kamakaula, Yohanes; Widati, Agatha W.; Pattiasina, Trees A.; Uria, Darmawanto (West Science Nature and Technology, 2025)
This study investigates the interrelationships among Ethnoecological Knowledge, Climate Adaptation Strategies, and Farmer Innovation in fostering Sustainable Agriculture in Indonesia. Using a quantitative approach, data were collected from 150 smallholder farmers across Java, Sumatra, and Sulawesi through structured questionnaires measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling (SEM-PLS 3) to test the direct, indirect, and mediating relationships among the constructs. The findings reveal that ethnoecological knowledge significantly enhances both climate adaptation and farmer innovation, indicating that traditional ecological wisdom remains a critical foundation for modern sustainability practices. Climate adaptation strategies have a dual role—directly strengthening sustainability and indirectly fostering innovation. Furthermore, farmer innovation mediates the relationship between traditional knowledge and sustainability, serving as a transformational bridge from cultural heritage to adaptive modernization. The model explains 69% of the variance in sustainable agriculture, confirming its strong predictive power. The study provides theoretical contributions by integrating the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT) and offers practical recommendations for policymakers to strengthen local wisdom, participatory innovation, and adaptive learning in rural development. These findings underscore that Indonesia’s agricultural transformation depends not on abandoning tradition, but on revitalizing it through innovation-driven adaptation toward sustainability.